Metabolic responses of the isopod Porcellionides pruinosus to nickel exposure assessed by H-1 NMR metabolomics - Ferreira, Nuno G. C.
This work aimed at characterizing the metabolome of the isopod Porcellionides pruinosus and at assessing its variations over 14 days under laboratory culture conditions and upon exposure to the contaminant metal Nickel (Ni). The spectral profiles obtained by H-1 NMR spectroscopy were thoroughly assigned and subjected to multivariate analysis in order to highlight consistent changes. Over 50 metabolites could be identified, providing considerable new knowledge on the metabolome of these model organisms. Several metabolites changed non-linearly with Ni dose and exposure time, showing distinct variation patterns for initial (4 days) and later time points (7 and 14 days). In particular, at day 4, several amino acids were increased and sugars were decreased (compared to controls), whereas these variations were inverted for longer exposure, possibly reflecting earlier and more intensive moulting. Other variations, namely in betaines and choline-containing compounds, were suggested to relate with osmoregulation and detoxification mechanisms. Ni also had a marked effect on several nucleotides (increased upon exposure) and a moderate impact on lipids (decreased upon exposure). Overall, this study has provided new information on the Ni-induced metabolic adaptations of the P. pruinosus isopod, paving the way for improved mechanistic understanding of how these model organisms handle soil contamination. Significance: This study provided, for the first time to our knowledge, a detailed picture of the NMR-detectable metabolome of terrestrial isopods and of its fluctuations in time and upon exposure to the contaminant metal Nickel. Several time- and dose-dependent changes were highlighted, providing mechanistic insight into how these important model organisms handle Ni contamination. (C) 2015 Elsevier B.V. All rights reserved.